Behavioral characteristics associated with 19p13.2 microdeletions. (16th July 2015) - Welham, Alice; Barth, Bursharan; Moss, Joanna; Penhallow, Jessica; Sheth, Krupa; Wilde, Lucy; Wynn, Sarah; Oliver, Chris
<x xml:space="preserve">Abstract</x> A small number of recent papers have described individuals with intellectual disabilities and microdeletions in chromosome band 19p13.2. However, little is known about the behavioral characteristics of individuals with microdeletions in this area. The current study examines behavioral characteristics of a series of 10 participants ranging in age from 2 to 20 years with 19p13.2 microdeletions. Parents/caregivers completed a series of established behavioral measures which have aided the elucidation of the behavioral phenotypes of a number of genetic neurodevelopmental syndromes. All but the youngest two participants (aged 2 and 3 years) were verbal, ambulant, and classified as "partly able" or "able" with regard to self‐help skills. Six of eight participants for whom a screening measure for autism spectrum disorders (ASD) could be deployed met criteria for an ASD. Six of the 10 participants had displayed self‐injurious behavior in the month prior to assessment, eight had displayed destruction/disruption of property, and eight had shown physically aggressive behaviors. Repetitive behaviors were prevalent in the sample (with all participants displaying at least one repetitive behavior to a clinically relevant level), as were problems with sleep. Low mood was not prevalent in this group, and nor were overactivity or impulsivity. Full determination of a behavioral phenotype for this group would require a larger sample size, distinguishing between genetic subtypes. However, the current data suggest that ASD characteristics, repetitive, and challenging behaviors (such as aggression and self‐injury) might be associated with 19p13.2 microdeletions, providing a basis for future investigation. © 2015 Wiley Periodicals, Inc.